Strain and electric field dependent variation in electronic and thermoelectric properties of PtS2 - Sohail Ahmad (Results in Physics, 2020)
Ab initio calculations based on plane wave methods show that the band gap of PtS2 depends on the number of monolayers combined by van der Waals (vdW) interactions or spin orbit correction (SOC). The valence band minimum (VBM) is sensitive to the out-of-plane, and conduction band maximum (CBM) to the in-plane lattice constants. The vdW force enhances the bonding out of plane, which in turn influences the bonding in plane. The band diagram gets splitted on application of SOC and hence resulting in decrease of band gap. On application of biaxial compressive and tensile strain, a variation in band gap from 1.54 eV to 1.08 eV & 0.97 eV and 1.06 eV & 1.04 eV is observed in case of bilayers with different stackings (AA & AB) respectively. A variation in band gap from 1.54 eV to 0.16 eV (0.23 eV) is also observed on applying electric field on AA(AB) bilayers of PtS2 in z-direction. Absence of imaginary frequencies in phonon dispersion of strained structure reflects the dynamical stability of the studied structure. The effects of strain on the thermoelectric properties of PtS2 monolayer and bilayer were also studied. A variation in the electrical conductivity is observed with the increase in strain in bilayers. As expected for thermoelectric application, the trend in the variation of Seebeck coefficient is of opposite nature. The present work demonstrates the flexibility available for tuning the electronic and thermoelectric properties of this material for a wide range of applications.